Peran Dan Pemikiran Syafi`i Antonio, Adiwarman Karim Dan Ma`ruf Amin Dalam Pengembangan Ekonomi Islam - Sudarmaji, Waluyo (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
In order to raise the spirit of Indonesian Muslims, it is very important to present the thoughts of these figures so that their thoughts can become a foundation that is then applied in real terms in the life of the nation and state. Among the figures who can be a source of inspiration are Muhammad Syafi`I Antonio, Adiwarman Azwar Karim and also KH. Ma`ruf Amin. The purpose of this study is to determine the Islamic economic thoughts of the three figures and to compare them. The study was conducted using a qualitative method using library research that was analyzed descriptively analytically. The results of the study show that the roles and thoughts of Syafi'i Antonio, Adiwarman Karim, and Ma'ruf Amin in the development of Islamic economics highlight their contributions in strengthening the foundations of the economy according to Islamic sharia principles. Syafi'i Antonio is known for his practical approach in the business and financial sectors, while Adiwarman Karim developed an in-depth theoretical analysis for Islamic economics globally and nationally. Ma'ruf Amin advocates for fair and inclusive economic policies at the social and political levels of Indonesia. Although their approaches are different, the unity of the three figures' thinking lies in the rejection of usury and an approach that emphasizes justice and blessings in economic distribution. Collectively, the three provide a strong foundation for the development of a sustainable and relevant Islamic economy for Muslims, facing challenges and opportunities in various global and local contexts.